On a singular Riemann–Liouville fractional boundary value problem with parameters - Tudorache, Alexandru; Luca, Rodica (Nonlinear Analysis: Modelling and Control, 2021)
We investigate the existence of positive solutions for a nonlinear Riemann–Liouville fractional differential equation with a positive parameter subject to nonlocal boundary conditions, which contain fractional derivatives and Riemann–Stieltjes integrals. The nonlinearity of the equation is nonnegative, and it may have singularities at its variables. In the proof of the main results, we use the fixed point index theory and the principal characteristic value of an associated linear operator. A related semipositone problem is also studied by using the Guo–Krasnosel’skii fixed point theorem.
Keywords: Riemann–Liouville fractional differential equation; nonlocal boundary conditions; positive parameter; singularities; positive solutions; semipositone problem